Comparative efficacy of albendazole, mebendazole and neem leaf extract in helminth infections in rat models (Dhaka University Journal of Biological Sciences, 2011)
Comparative efficacy of Albendazole, Mebendazole and neem leaf extract (Azadirachta indica) against Vampirolepis nana, Hymenolepis diminuta and Syphacia muris infections in laboratory rat strain Long-Evans (Rattus norvegicus Berkenhout, 1769) was evaluated. After treating with the drugs, egg reduction rate and cure rate from the worm infection were observed. Mebendazole had greater efficacy in terms of cure rate against H. diminuta, but in terms of egg reduction rate in H. diminuta infection, Albendazole had greater efficacy. The relative efficacy of Albendazole and Mebendazole were similar in terms of cure rate for S. muris infection (33.33%). In case of H. diminuta, both Albendazole and Mebendazole had nearly similar efficacy in terms of cure rate (20% vs. 25%). Albendazole had greater efficacy in terms of cure rate and egg reduction rate against V. nana than Mebendazole (25% vs. 16.67% and 28.57% vs. 10%). In case of S. muris infection, Mebendazole showed the higher egg reduction rate than Albendazole (20.09% vs 14.52%). Neem leaf extract had better efficacy on egg reduction rate in case of S. muris infection than Albendazole and Mebendazole. The relative efficacy of the neem extract was higher than that of the administred chemotherapy.Key words: Long-Evans; Rattus norvegicus; Comparative; Efficacy; Albendazole; Mebendazole; Neem leaf extractDOI: http://dx.doi.org/10.3329/dujbs.v20i1.8836Dhaka Univ. J. Biol. Sci. 20(1): 41-48, 2011 (January)